2016
DOI: 10.4172/2329-6607.1000178
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Elastase Treatment of Cephalic Veins

Abstract: Background Vessel injury at the time of Arteriovenous Fistula (AVF) creation may lead to neointimal hyperplasia that impairs AVF maturation. Vonapanitase, a recombinant human chymotrypsin-like elastase family member 1, is an investigational drug under development to improve AVF maturation and patency. The current studies were designed to document vonapanitase effects in human cephalic veins that are used in AVF creation. Methods Human cephalic veins were mounted on a perfusion myograph. Vonapanitase 1.2, 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…19 Vonapanitase applied topically immediately following fistula creation rapidly enters the outermost adventitial vessel layer where it fragments elastin fibers. 20,21 Elastin fragmentation by endogenous elastases (matrix metalloproteinases) is an early and essential component of outward vascular remodeling in animal fistula models. 22 Previous clinical trials had shown that vonapanitase, when administered at doses that partially fragment elastin in human arm veins, may increase fistula and arteriovenous graft blood flow 23,24 and improve fistula maturation, patency, and use for hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…19 Vonapanitase applied topically immediately following fistula creation rapidly enters the outermost adventitial vessel layer where it fragments elastin fibers. 20,21 Elastin fragmentation by endogenous elastases (matrix metalloproteinases) is an early and essential component of outward vascular remodeling in animal fistula models. 22 Previous clinical trials had shown that vonapanitase, when administered at doses that partially fragment elastin in human arm veins, may increase fistula and arteriovenous graft blood flow 23,24 and improve fistula maturation, patency, and use for hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…19 When vonapanitase is applied locally during fistula creation, it is rapidly absorbed into the outermost vessel layer, where it fragments elastin fibers. 20,21 Elastin fragmentation by endogenous elastases (matrix metalloproteinases) is an early and essential component of outward vascular remodeling in animal fistula models. 22 Elastin fragments (peptides) created by CELA1 have chemotactic properties that may inhibit cell migration to the intima.…”
mentioning
confidence: 99%
“…However, it failed to show a reduction in NH at 21 days in a 12‐pig AVG study (Burke et al, 2009), and recently failed to achieve statistical significance on both of its coprimary endpoints in a second Phase III clinical trial (PATENCY‐2) seeking to improve maturation and patency of AVFs. These results may underpin the importance of providing a more sustained effect with an external sheath, perhaps with a slowly biodegradable SMP wrap that promotes MMP‐12 expression periadventitially, rather than with a therapeutic that may exude only short‐term effects (catalytic activity of 1–4 hr) (Wong et al, 2016). Further in‐depth studies are required to confirm and elucidate the role that MMP‐12 might play in the neovascular, inflammatory, and fibrogenic responses to these macroporous SMP scaffolds.…”
Section: Discussionmentioning
confidence: 99%